Pendampingan Pengelolaan Sungai Gelis di Desa Rahtawu, Pegunungan Muria - Mochamad Widjanarko; Mohammad Khasan; Ahmad Faqihuddin; Dian Wismar’ein (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Rahtawu Village is traversed by the Gelis River, one of the major rivers originating in the Muria Mountains. The village’s location beneath the peak of Mount Muria (29) offers picturesque landscapes in the surrounding hills, attracting visitors from outside the village. However, the community has yet to maximize the potential of this natural beauty. The objective of this community service is twofold. Firstly, to inform about the regulations concerning the Gelis River buffer zones in Rahtawu Village, Kudus Regency. Secondly, to recommend ecotourism assistance in the Muria region, particularly in Rahtawu Village, Kudus Regency. This assistance employs a policy support approach, directed group discussions, and the creation of posters. Following these assistance activities, it can be concluded that, after receiving explanations from the River Basin Management Agency (BBWS) Pemali Juana, the Rahtawu Village government, along with village officials and other group members, now understands the root issues regarding the use of Gelis River buffer zones in Rahtawu Village, Kudus Regency. They express a desire to manage ecotourism in their area.